O efeito do ultrassom na biodisponibilidade de compostos bioativos de frutas amazônicas - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
Ultrasound plays a crucial role in maximizing the release of bioactive compounds, promoting efficiency, nutrient preservation, and offering advantages in terms of productivity, yield, and selectivity. It also reduces chemical and physical risks while being environmentally friendly, contributing to more sustainable practices in releasing bioactive compounds from fruit juices. In comparison to other techniques such as pressing, solvent extraction, decoction, and Soxhlet extraction, which have low selectivity, long processing times, and high reagent consumption, ultrasound stands out.Various techniques for extracting and releasing bioactive compounds in Amazonian fruit juices, such as electric field pressure, pressing, solvent extraction, and Soxhlet extraction, currently exist. Despite scientific advances in the use of this emerging technique, little attention has been given to ultrasound in extracting bioactive compounds from Abricó (Mammea americana L.), Cubiu (Solanum sessiliflorum Dunal), and Mari-mari (Cassia leiandra banth) fruits, including their in vitro bioavailability and digestibility.This study focused on evaluating the use of ultrasound in the bioavailability of bioactive compounds from Abricó (AB), Cubiu (CB), and Mari-mari (MM) fruits. These species are typical of the Northern region, rich in fibers, bioactive compounds, antioxidants, Vitamins A, B, and C, and minerals, and are commonly used in traditional medicine as digestive aids. Physical-chemical analyses, including pH, color, soluble solids, titratable acidity, centesimal composition, and mineral content, were conducted. Chemical analyses included total phenolic compounds, antioxidant activity using DPPH, ABTS, and FRAP methods, carotenoids, and molecular absorption spectroscopy through UV-Visible and Fourier-transform infrared spectroscopy with attenuated total reflectance (FTIR-ATR) to observe electronic transitions and vibrational modes of specific functional groups. Results from color analysis showed significant differences in L*, a*, b* parameters with 40% sonication for AB and CB. Centesimal content revealed higher moisture content (15.49%) in AB juice and lower lipid content in CB and MM juices (0.75%), respectively. Bioactive compounds were released in AB and CB juices, as indicated by significant total phenolic content (7.26 ± 1.03 mg GAE/mL), antioxidant capacity assessed by DPPH (1204 ± 3.82 and 1125 ± 3.63 μmol TE/100 mL) at 60% power for AB and CB. The influence of sonication on MM juice was negligible. ABTS (2028.55 ± 4.44 μM/TE) was prominent in untreated MM juice. At 60% power, AB and CB showed (1464 ± 0.76 μmol trolox/mL), with a 20% reduction for AB (316 ± 3.33 μmol trolox/mL) in FRAP. Carotenoids (200 ± 0.80 and 146 ± 31.0 μg/mL β-carotene equivalents) were recorded at 60% power for CB and AB. FTIR-ATR chemical characterization revealed significant changes in spectra after ultrasound treatment, including electronic transitions of π - π* and a weak absorption band shifting from 283 to 285 in the carbonyl group region, indicating shorter wavelengths with increased carbonyl group polarity. The study suggests that 60% ultrasound extraction is viable, costeffective, and environmentally friendly for releasing phenolic and carotenoid-rich compounds Future studies will be dedicated to conducting additional chemical and microbiological characterization analyses to identify, quantify, and assess the stability of the treated juices.
The effect of ultrasound on the bioavailability of compounds bioactives from amazonian fruits
Keywords: .; .; .; CIENCIAS EXATAS E DA TERRA; Frutas amazônicas; Ultrassom; Compostos bioativos; Biodisponibilidade; Digestibilidade